Urchin-like Co3O4 as a heterogenous peroxymonosulfate catalyst for crystal violet degradation: Reaction kinetics and process optimization. (December 2022) - Li, Bo; Dai, Li-Yuan; Wang, Wei-Song; Xu, Huan-Yan
Abstract: Advanced oxidation processes based on the sulfate radicals (SR-AOPs) have been considered as promising methods to eliminate the organic contaminants from wastewater. In this work, the urchin-like Co3 O4 was prepared and developed as an efficient heterogenous catalyst to activate peroxymonosulfate (PMS) for the degradation of an active dye, crystal violet (CV). The morphological observations by SEM and TEM confirmed a distinct urchin-like structure of as-prepared Co3 O4 sample. XRD pattern indicated that all the characteristic diffraction peaks belonged to Co3 O4 with the face-centered-cubic spinel structure. The contrast experiments showed that the CV degradation efficiency in urchin-like Co3 O4 /PMS system was much higher than that in pristine PMS or Co3 O4 system, suggesting that PMS could be effectively activated by the urchin-like Co3 O4 for CV degradation. Kinetic studies revealed that CV degradation reaction in urchin-like Co3 O4 /PMS system followed the retarded first-order model. The process optimization of CV degradation was implemented by response surface methodology (RSM), and then the optimum conditions were determined. Graphical Abstract: ga1 Highlights: Specific urchin-like Co3 O4 was designed and employed for PMS activation. The detailed reaction kinetics study reflects the complexity of the degradation process. The process of degradation was further optimized via response surface methodology.